Evaluation of the physicochemical properties and adhesive interface quality of BioRoot Flow and BioRoot RCS endodontic sealers: An in vitro study - Dione Tavares Reis; Gustavo Alexandre de Castro-Vasconcelos; Gustavo Creazzo; Helena Cristina de Assis; Igor Bassi Ferreira Petean; Manoel Damiao de Sousa-Neto; Jardel Francisco Mazzi-Chaves; Fabiane Carneiro Lopes-Olhê (Clinical Oral Investigations, 2026)
Abstract Objective Bioceramic sealers have been increasingly used in endodontics due to their favorable physicochemical and biological properties. However, evidence regarding the physicochemical properties, push-out bond strength, and adhesive interface characteristics of BioRoot Flow compared with other root canal sealers remains limited. Therefore, this study evaluated the physicochemical properties, push-out bond strength, failure pattern, and adhesive interface quality of BioRoot Flow (BRF), BioRoot RCS (BRR), and the epoxy resin–based sealer AH Plus (AHP). Methods Setting time, dimensional change, solubility, radiopacity, and flow were assessed following ANSI/ADA Specification No. 57. Setting time was recorded using cylindrical molds tested with a Gillmore needle. Dimensional change was measured in five specimens per sealer before and after 30 days in distilled water. Solubility was assessed in ten specimens after seven days of immersion, followed by desiccation. Radiopacity was evaluated using acrylic plates radiographed beside an aluminum step wedge. Flow was assessed according to ANSI/ADA standards. For bond strength and interface analysis, thirty single-rooted teeth were prepared with the Reciproc system and irrigated with sodium hypochlorite and EDTA. Canals were obturated with the single-cone technique using the tested sealers ( n = 10). Three slices were obtained from each root third; two were used for push-out testing and failure analysis, and one for confocal laser scanning microscopy. Results AHP showed the shortest setting time, highest radiopacity, and greatest flow. BRF exhibited the highest solubility, while dimensional change did not differ among materials. Bond strength varied significantly among sealers and root thirds; AHP presented the highest values, followed by BRF and BRR. Adhesive failures predominated for AHP, whereas bioceramic sealers showed mainly mixed failures. Conclusion AHP demonstrated superior physicochemical properties, higher bond strength, and better adhesive interface adaptation. BRF performed better than BRR regarding bonding and interface quality.